The Development of a Hybrid Learning Management System with Learning Styles for Creative Learning to Undergraduate Students - Anugrah, Septriyan; Supendra, Dedi; Jalinus, Nizwardi; Syahril, Syahril; Austin, Diah Anggraini (JOIV : International Journal on Informatics Visualization, 2025)
Distance learning often poses challenges for teachers, particularly in understanding the diverse learning styles of their students. The inability to recognize and accommodate these differences can lead to monotonous teaching approaches, which hinder students' comprehension and creativity. This study aims to evaluate the application of learning style concepts developed by Peter Honey and Alan Mumford, implemented in a Learning Management System (LMS) designed by the researcher to support creative learning practices. The research method used is research and development with the Plomp model. This study involved 219 students enrolled in an introductory programming course at Universitas Negeri Padang. The results indicate that respondents' experiences in six aspects—attractiveness, clarity, efficiency, reliability, stimulation, and novelty—received favorable evaluations. This study emphasizes the importance of understanding students' learning styles and using appropriate media to create an environment that supports exploring ideas and innovation, enabling students to develop their creativity optimally while ensuring equal opportunities for all students to grow and succeed.